Quantitative Analysis of the Subsidence Trough of the Barapukuria Coal Mine, Bangladesh (American Journal of Innovation in Science and Engineering, 2024)
Subsidence has been an ever-increasing concern of the Barapukuria coal mine for nearly two decades and has indeed called for quantification to predict the expansion of surface subsidence. The study has been undertaken to address this issue. Earlier studies only dealt with the horizontal expansion of the subsidence trough and were calculated based on a rudimentary rule of thumb. On this basis, about 646 acres of land have been acquired and marked as the Influence zone of the mine. However, the extension of the subsidence trough has moved further beyond the Influenced-zone boundary, severely damaging several houses around the mine . This study empirically measures the spatial extension of the subsidence trough identifying mining-induced cracks and joints in 37 affected houses around the mine that emphasized the modification of the rule of thumbs, particularly the angle of draw. It is revealed that the minimum and maximum limit angles are 42o and 60o respectively, and a distance of 378m to 727m (average 552m) must be considered to mark the influenced-zone boundary of the mine while the mining depth is 420m. To precisely quantify and predict the increasing progression of subsidence trough, it is imperative to determine an angle of draw, spatial and areal expansion, and the geotechnical properties for this specific mine.